Upaya Meningkatkan Pemahaman Siswa Kelas V Sekolah Dasar terhadap Operasi Perkalian Pecahan Desimal - Goenawan Roebyanto (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
This classroom action research aimed at helping students increase their understanding toward multiplication operation of decimal fractions. The subjects of this study were 3 five graders of Madyopuro and Sawojajar Malang Elementary School whose mathematics achivement was low. This study found the students mistakes and the causes which were done by students in understanding fraction of the same value, changing fraction, and multiplication operation of decimal fractions. Learning to compute multiplication operation of decimal fraction was done by introducing them to 3 ways or steps. First, changing decimal fractions to simple fractions, across, and down, could increase the students’ understanding about multiplication operation of decimal fraction.